2011
DOI: 10.1105/tpc.111.089300
|View full text |Cite
|
Sign up to set email alerts
|

The JAZ Proteins: A Crucial Interface in the Jasmonate Signaling Cascade

Abstract: Jasmonates are phytohormones that regulate many aspects of plant growth, development, and defense. Within the signaling cascades that are triggered by jasmonates, the JASMONATE-ZIM DOMAIN (JAZ) repressor proteins play a central role. The endogenous bioactive JA-Ile conjugate mediates the binding of JAZ proteins to the F-box protein CORONATINE INSENSITIVE1 (COI1), part of the Skp1/Cullin/F-box SCF COI1 ubiquitin E3 ligase complex. Upon the subsequent destruction of the JAZ proteins by the 26S proteasome, multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
451
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 545 publications
(479 citation statements)
references
References 94 publications
5
451
2
2
Order By: Relevance
“…Interestingly, in contrast to most of the known JAZ-TF interaction pairs, in which the Jas domain of JAZ proteins and the transcription activation domain of TFs are involved in JAZ-TF interaction (reviewed in Pauwels and Goossens, 2011), we found that the NT domain of JAZ1 and the AP2 domain of TOE1 are involved in the JAZ1-TOE1 interaction. This might reflect that JAZ proteins can adopt diverse mechanisms to attenuate the function of their interacting TFs in a context-specific manner.…”
Section: Discussioncontrasting
confidence: 86%
“…Interestingly, in contrast to most of the known JAZ-TF interaction pairs, in which the Jas domain of JAZ proteins and the transcription activation domain of TFs are involved in JAZ-TF interaction (reviewed in Pauwels and Goossens, 2011), we found that the NT domain of JAZ1 and the AP2 domain of TOE1 are involved in the JAZ1-TOE1 interaction. This might reflect that JAZ proteins can adopt diverse mechanisms to attenuate the function of their interacting TFs in a context-specific manner.…”
Section: Discussioncontrasting
confidence: 86%
“…1-2). Several genes corresponding to potential regulatory factors had maximal transcriptional upregulation prior to or concurrent with that of the triterpene saponin genes, including a MYC-like bHLH protein and the JAZ repressor proteins, known elements of the core JA signaling module [4][5][6] , as well as a gene (MT067) corresponding to an RMA-like E3 Ub-ligase 10 , denominated MAKIBISHI1 (MKB1) (Extended Data Fig. 3).…”
mentioning
confidence: 99%
“…Under water-sufficient conditions, only 49 genes showed more than a 2-fold change in expression, of which 35 were up-regulated and 14 were down- regulated in the cych;1 RNAi#7 mutant ( Table I). The microarray results indicated increased transcript levels of ARABIDOPSIS RIBULOSE-BISPHOSPHATE CAR-BOXYLASE/OXYGENASE X1 (ATRBCX1) (Kolesinski et al, 2011), ECERIFERUM1 (CER1) (Bourdenx et al, 2011), JASMONATE-ZIM-DOMAIN PROTEIN5 (JAZ5; Pauwels and Goossens, 2011), LIPID TRANSFER PROTEIN2 (LTP2; Chae et al, 2010), and At1g06620 in the cych;1 RNAi#7 mutant, all of which can be induced by water deprivation. Interestingly, the 35 upregulated genes included at least 12 genes involved in redox homeostasis (i.e.…”
Section: Downstream Targets Of Cych;1mentioning
confidence: 99%